Early Stage Prurigo Pigmentosa : A Case Report - Emel ONAYGİL; Abdullah SONGUR; Zekayi KUTLUBAY; Cuyan DEMİRKESEN (Türk Patoloji Dergisi, 2018)
Prurigo pigmentosa is a rare inflammatory dermatosis that primarily affects adolescents and young adults. Even though it is most commonly seen in Japanese women, other countries have reported cases with increasing frequency. It is characterized by erythematous papules and macules on the trunk, neck and chest that resolve leaving a reticulate hyperpigmentation. Some endogenous factors related with ketosis like fasting, diet, diabetes, pregnancy and exogenous agents like chrome, nickel, para-amino compounds have been accused of playing a role in etiology. Here we would like to present a case of a 16-year-old female patient who was referred to our clinic with pruritic lesions on the trunk and neck, consistent with the initial phase of prurigo pigmentosa, after a period of strict diet. Prurigo pigmentosa is a disease with distinctive histologic and clinical features. Due to its rare occurrence, an accurate diagnosis may be particularly challenging. Clinicopathological correlation is therefore crucial in the diagnosis of the disease in its early phase.